Application Of Economic Mathematics In Periodical Installation System - Ismail, Muhammad Iqbal Al-Banna; Hernawati, Depie; Supena, Yusup (iora, 2022)
This paper provides financial planning aspect by modeling the impact of mortgage rate changes on the size of payments for ARMS. This study uses a simulation approach to model the choice between a fixed rate mortgage (FRM and an adjustable rate mortgage (ARM). Our simulations help assess therisks and benefits of choosing an ARM rather than a FRM. We represent the risk of the ARM with distributions of present value cost for a variety of mortgage lifeperiods.